1986
DOI: 10.1203/00006450-198604000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Chain Triglycerides in Infant Formulas and their Relation to Plasma Ketone Body Concentrations

Abstract: A B S T R A a . A mild ketosis is known to prevail in the mother, fetus, and newborn infant during the 3rd trimester and in the early neonatal period. It has been shown that during an equivalent period in the rat ketone bodies are readily oxidized and serve a s key substrates for lipogenesis in brain. Since medium-chain triglycerides are known to be ketogenic, preterm infants may benefit from dietary medium-chain triglycerides beyond the point of enhanced fat absorption. Our objective was to determine the keto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
4

Year Published

1987
1987
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 17 publications
0
10
0
4
Order By: Relevance
“…When there is excess acetyl-CoA, a major pathway is formation of ketone bodies; in fact, MCFA are known to be ketogenic (26). Feeding of an MCT-containing formula for 4 d promotes a mild ketosis in preterm infants (27). These ketone bodies will be quickly utilized peripherally, especially after a period of adaptation (28).…”
Section: Resultsmentioning
confidence: 99%
“…When there is excess acetyl-CoA, a major pathway is formation of ketone bodies; in fact, MCFA are known to be ketogenic (26). Feeding of an MCT-containing formula for 4 d promotes a mild ketosis in preterm infants (27). These ketone bodies will be quickly utilized peripherally, especially after a period of adaptation (28).…”
Section: Resultsmentioning
confidence: 99%
“…Early studies on polyols such as 1,2-, 1,4-, and 2,3-butanediols revealed that they and monounsaturated FAs ( 61 ). Also, incorporation of MCTG into the KD may be helpful in formulating more tolerable ketogenic regimens for the long-term treatment of drug-resistant epilepsy (62)(63)(64)(65).…”
Section: Kesmentioning
confidence: 99%
“…In comparison to long-chain triacylglycerols (LCT), MCT are more efficiently absorbed in the digestive tract, and the liberated medium chain fatty acids (MCFA) are extensively and rapidly oxidized, whereas long chain fatty acids (LCFA) are largely stored in tissues (5). The intense lipid oxidation is associated with a ketogenic effect of dietary MCT, which provides an alternative energy source and is considered harmless for the infant as long as ketone body concentrations do not exceed values observed in breast fed infants (5,6).…”
mentioning
confidence: 99%